Regression of liver fibrosis after curing chronic hepatitis C with oral antivirals in patients with and without HIV coinfection. (23rd October 2018) - Lledó, Gema M.; Carrasco, Itziar; Benítez-Gutiérrez, Laura M.; Arias, Ana; Royuela, Ana; Requena, Silvia; Cuervas-Mons, Valentín; de Mendoza, Carmen
Abstract : Background: Treatment with direct-acting antivirals (DAA) eradicates hepatitis C virus (HCV) from most chronic carriers. Information on regression of liver fibrosis and the influence of HIV is scarce in cured patients. Methods: All consecutive HCV-infected individuals treated with DAA at our institution were examined. Hepatic elastography was performed at baseline and at the time of SVR12. Liver fibrosis regression was defined as a shift from advanced fibrosis (Metavir F3-F4) to null–mild fibrosis (F0–F2) and/or a reduction greater than 30% kPa. AST to platelet ratio index (APRI) and fibrosis 4 (FIB-4) scores were calculated in parallel. Results: A total of 260 patients were treated with DAA. All but 14 achieved SVR12 and represented the study population. HIV confection was present in 42%. At baseline, 57.2% had advanced liver fibrosis with a median of 11 kPa, FIB-4 of 2.4, and APRI of 0.95. At the time of SVR12, a median reduction of 2.1 kPa ( P  < 0.001) was recognized using elastography. A significant fibrosis regression was seen in 40%, being more frequent in patients with baseline advanced fibrosis than in those with null–mild fibrosis (52.3 vs. 22.5%; P  < 0.001). Even so, 41.2% of patients with baseline F3–F4 kept within cirrhotic scores. In multivariable analysis, only baseline stiffness was significantly associated with the extent of liver fibrosis regression. Conclusion: HCV cure with DAA is associated with regression of liver fibrosis in most patients treated with DAA, as measured using elastography, FIB-4 and APRI. This benefit is more pronounced in patients with baseline advanced fibrosis and cirrhosis. The dynamics of liver fibrosis regression are not influenced by HIV coinfection.